STRATEGI KOMUNIKASI INTERPERSONAL DALAM MEMBANGUN HUBUNGAN GURU DENGAN SISWA - Fara Nabila Tania; Malika Aulia Husnah S; Dimas Dwika Syahrahmanda; Afwan Syahril Manurung (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Interpersonal communication strategies have an important role in building harmonious relationships between teachers and students in the educational environment. This research aims to analyze how interpersonal communication strategies are applied by teachers to create positive relationships, support the learning process, and increase student engagement. The method used is a qualitative approach with data collection through observation, interviews and literature study. The research results show that openness, empathy, supportive attitudes, respect, and positive attitudes are key elements in interpersonal communication between teachers and students. This strategy is able to build trust, increase learning motivation, and create a conducive learning environment.